2017
DOI: 10.15503/jecs20171.62.78
|View full text |Cite
|
Sign up to set email alerts
|

In search of transformative moments: Blending community building pursuits into lifelong learning experiences

Abstract: This article presents an exploration of the relationship between community building and lifelong learning. Using a reflective style, the authors propose that the fusion of community building principles with lifelong learning practice can positively transform educational practice. Seven positive pursuits are highlighted regarding their potential to assist the implementation of community building into lifelong learning programs: (1) asset-based thinking; (2) critical reflection; (3) systems thinking; (4) cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…One answer may be transformation. Participation in lifelong learning is an indispensable pursuit for older adults to remain active, cognitively and socially (Pstross et al 2017). A social and cognitive transformation perspective helps address the transformative power of lifelong learning in the lives of women in older adult learning communities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One answer may be transformation. Participation in lifelong learning is an indispensable pursuit for older adults to remain active, cognitively and socially (Pstross et al 2017). A social and cognitive transformation perspective helps address the transformative power of lifelong learning in the lives of women in older adult learning communities.…”
Section: Resultsmentioning
confidence: 99%
“…Lamb and Brady (2005) identify sense of belonging, enhanced self-esteem, and spiritual renewal as complementary motives for enrollment and participation in lifelong learning institute programs across multiple institutions. The transformational power of lifelong learning attracts older adult leaners to and engages them in lifelong learning institutes and programs (Pstross et al 2017).…”
Section: Transforming (Women) Through Lifelong Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a prompt to facilitate rhythms of praxis in the work to produce, promote and restore Solidarity and Agency. Praxis-based approaches emphasize personal experience as the basis for reflection (Freire, 1970(Freire, /2012Ledwith, 2011;Pstross et al, 2017). In contrast to approaches that have downplayed the importance of the body or the political nature of the mundane or domestic life, the CPCD is centered on the lived experiences of people (Peterson, 2018).…”
Section: Catalytic Action Through a Cycle Of Praxismentioning
confidence: 99%
“…In the past 20 years, the literature on the benefits of lifelong learning has grown significantly (Coleman, 2017). The social and community benefits of lifelong learning include those of asset-based thinking and creative expression (Pstross, 2017), as well as a sense of ownership and sustained relationships (Brady, 2013). In addition, studies have shown that older learners generally report positive wellbeing and healthy lifestyles, i.e., non-smoking and regular exercise (Narushima, 2018).…”
Section: The Benefits Of Lifelong Learningmentioning
confidence: 99%